Visualisasi Banalitas Kejahatan Dalam Seni Lukis - Jayanata, Banny (Institut Seni Indoensia Surakarta, 2013)
According to crimes which happens belong to our lives, crimes always give effects and impacts in our daily life as human being. Despite we have some feelings about crimes as a negative side of life, we should not beingso full-ignorance on it. Crime has its values like some moralities have. Ignore crime only make itmore invisible and undetected, by other name: make it more dangerous. In this project, writer means to bring crime into surface of life, using art for its medium. By art, we can express so many ideas and feelings we have, without being explicit showing or critisyzing. Crimes can be seen in a different way, not always in a dicotomic way: opposite of a goodness and beautiness.Keywords: Crime, banality, violence, art and painting.